Brachial artery responses to acute hypercapnia: The roles of shear stress and adrenergic tone. Issue 12 (27th September 2022) - Carr, Jay M. J. R.; Ainslie, Philip N.; Howe, Connor A.; Gibbons, Travis D.; Tymko, Michael M.; Steele, Andrew R.; Hoiland, Ryan L.; Vizcardo‐Galindo, Gustavo A.; Patrician, Alex; Brown, Courtney V.; Caldwell, Hannah G.; Tremblay, Joshua C.
Abstract : New Findings: What is the central question of this study? What are the contributions of shear stress and adrenergic tone to brachial artery vasodilatation during hypercapnia? What is the main finding and its importance? In healthy young adults, shear‐mediated vasodilatation does not occur in the brachial artery during hypercapnia, as elevated α₁‐adrenergic activity typically maintains vascular tone and offsets distal vasodilatation controlling flow. Abstract: We aimed to assess the shear stress dependency of brachial artery (BA) responses to hypercapnia, and the α₁‐adrenergic restraint of these responses. We hypothesized that elevated shear stress during hypercapnia would cause BA vasodilatation, but where shear stress was prohibited (via arterial compression), the BA would not vasodilate (study 1); and, in the absence of α₁‐adrenergic activity, blood flow, shear stress and BA vasodilatation would increase (study 2). In study 1, 14 healthy adults (7/7 male/female, 27 ± 4 years) underwent bilateral BA duplex ultrasound during hypercapnia (partial pressure of end‐tidal carbon dioxide, +10.2 ± 0.3 mmHg above baseline, 12 min) via dynamic end‐tidal forcing, and shear stress was reduced in one BA using manual compression (compression vs. control arm). Neither diameter nor blood flow was different between baseline and the last minute of hypercapnia ( P = 0.423, P = 0.363, respectively) in either arm. The change values from baseline to the last minute, in diameter (%; P = 0.201), flow (ml/min; P = 0.234) and conductance (ml/min/mmHg; P = 0.503) were not different between arms. In study 2, 12 healthy adults (9/3 male/female, 26 ± 4 years) underwent the same design with and without α₁‐adrenergic receptor blockade (prazosin; 0.05 mg/kg) in a placebo‐controlled, double‐blind and randomized design. BA flow, conductance and shear rate increased during hypercapnia in the prazosin control arm (interaction, P < 0.001), but in neither arm during placebo. Even in the absence of α₁‐adrenergic restraint, downstream vasodilatation in the microvasculature during hypercapnia is insufficient to cause shear‐mediated vasodilatation in the BA.